2012
DOI: 10.1021/la3001703
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Protein Synthesis inside Giant Unilamellar Vesicles Analyzed by Flow Cytometry

Abstract: Lipid vesicles have been used as model cell systems, in which an in-vitro transcription-translation system (IVTT) is encapsulated to carry out intravesicular protein synthesis. Despite a large number of previous studies, a quantitative understanding of how protein synthesis inside the vesicles is affected by the lipid membrane remains elusive. This is mainly because of the heterogeneity in structural properties of the lipid vesicles used in the experiments. We investigated the effects of the phospholipid membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(160 citation statements)
references
References 38 publications
5
155
0
Order By: Relevance
“…The difference in the vesicle volume may affect the intravesicular protein synthesis, for example, by creating a difference in the ratio of the surface area to the volume. This was not the case, because our previous report indicated that GFP synthesis using 1 nM DNA inside the GUV proceeded similarly regardless of the vesicle volume (21). Furthermore, the volume distribution of the vesicle did not change significantly during the protein synthesis (5-h incubation at 37°C) (Fig.…”
Section: Significancementioning
confidence: 74%
See 3 more Smart Citations
“…The difference in the vesicle volume may affect the intravesicular protein synthesis, for example, by creating a difference in the ratio of the surface area to the volume. This was not the case, because our previous report indicated that GFP synthesis using 1 nM DNA inside the GUV proceeded similarly regardless of the vesicle volume (21). Furthermore, the volume distribution of the vesicle did not change significantly during the protein synthesis (5-h incubation at 37°C) (Fig.…”
Section: Significancementioning
confidence: 74%
“…ii) Conditions appropriate for the target membrane protein can be adopted because the lipid composition of the GUVs is adjustable. We have shown previously that GUVs with different lipid compositions can be used without affecting intravesicular protein synthesis (21), indicating that a wide range of membranes may be used for liposome display. iii) Conditions appropriate for the target membrane protein can be adopted because the intravesicular solution can be adjusted as needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other numerous applications of the compartmentalized PS were focused on understanding gene expression inside liposomes, such as in the presence of different membrane lipid composition [10], with different preparation methods [11], and in different-sized vesicles [12].…”
Section: Introductionmentioning
confidence: 99%